Sikap Pentadbir Sekolah Terhadap Penggunaan Komputer dalam Pentadbiran - Ahmad Rafee, Che Kassim (1998)
The purpose of this study was to examine variables that could influence attitudes toward using computers among school administrators in Larut, Matang and Selama District, Perak Darul Ridzuan. The variables investigated in this study were gender, age, computer skills and experience, computer access, and training. The instrument used for this study was the Computer Attitude Scale (CAS). The CAS is a 40-item instrument that is divided into four, 1 O-item subscales: Computer Anxiety, Computer Confidence, Computer Liking, and Computer Usefulness. These four subscales were used to describe the four dimensions of attitudes toward computers. The findings significantly revealed that computer access and training, statistically influenced attitudes toward using computers, whereas gender, age, computer skills and experience, did not. Therefore, the conclusions and recommendations based on the findings of this study indicated that proper training and better computer facilities should be provided by the authorities to teachers and school administrators in order to enhance the computer usage in schools, and to increase the integration of information technology in education in Malaysia.